2021
DOI: 10.1002/clc.23593
|View full text |Cite
|
Sign up to set email alerts
|

The impact of underweight and obesity on outcomes in anticoagulated patients with atrial fibrillation: A systematic review and meta‐analysis on the obesity paradox

Abstract: Although obesity is associated with the development and progression of atrial fibrillation (AF), an obesity paradox may be present, illustrated by seemingly protective effects of obesity on AF‐related outcomes. Body mass index (BMI) has an impact on outcomes in AF patients using oral anticoagulants. After searching Medline and Embase, meta‐analysis of results of four randomized and five observational studies demonstrated significantly lower risks of stroke or systemic embolism (RR 0.80, 95%CI [0.73–0.87]; RR 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…Obesity is a risk factor for ischemic stroke; its effect on treatment outcomes in AIS patients is unclear [ 45 ]. The description of obesity categories is based on body mass index (BMI), and a U-shaped association between BMI and stroke has been reported [ 46 ]. However, other studies [ 47 , 48 ] support the paradoxical concept of relative longevity in obese patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a risk factor for ischemic stroke; its effect on treatment outcomes in AIS patients is unclear [ 45 ]. The description of obesity categories is based on body mass index (BMI), and a U-shaped association between BMI and stroke has been reported [ 46 ]. However, other studies [ 47 , 48 ] support the paradoxical concept of relative longevity in obese patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Using a simple search, we found 14 meta-analyses that also explored the association between BMI and mortality: 3 each in heart failure [193][194][195] and percutaneous coronary intervention, [196][197][198] 1 in atrial fibrillation, 199 1 in acute coronary syndrome, 200 1 in aortic stenosis, 201 1 in type 2 diabetes, 202 1 in colorectal cancer, 203 1 in lung cancer, 204 1 in acute respiratory distress, 7 and 1 in pneumonia. 205 All found that BMI in the overweight and obesity range was associated with significantly lower mortality as compared to BMI 18-25 kg/m 2 .…”
Section: Support From Other Studiesmentioning
confidence: 99%
“…Current available evidence on NVAF patients with UW presents contradictory results [12][13][14][15][16][17]. Data derived from a meta-analysis by Grymonprez et al demonstrated a significant higher incidence of stroke or thromboembolic events and mortality risks in UW NVAF populations.…”
Section: Introductionmentioning
confidence: 99%